Cell Dynamic Simulations of Diblock Copolymer/Colloid Systems. Issue 1 (29th August 2016) - Díaz, Javier; Pinna, Marco; Zvelindovsky, Andrei V.; Asta, Adelchi; Pagonabarraga, Ignacio
Abstract : Cell Dynamic Simulation combined with Brownian Motion are used to describe a mixture of block copolymer and nanoparticles, respectively. The changes in the morphology of the matrix are studied when including colloids, as well as its assembly depending on their size and affinity with one of the blocks. Several experiments are reproduced. Abstract : The presence of nanoparticles in a diblock copolymer leads to changes in the morphology and properties of the matrix and can produce highly organized hybrid materials. The resulting material properties depend not only on the polymer composition but also on the size, shape, and surface properties of the colloids. The dynamics of this kind of systems using a hybrid mesoscopic approach has been studied in this work. A continuum description for the polymer is used, while colloids are individually resolved. The method allows for a variable preference of the colloids, which can have different sizes, to the different components the block copolymer is made of. The impact that the nanoparticle preference for either, both, or none of the blocks has on the collective properties of nanoparticle–block copolymer composites can be analyzed. Several experimental results are reproduced covering colloid‐induced phase transition, particles' placement within the matrix, and the role of incompatibilities between colloids and monomers.